2016
DOI: 10.1523/jneurosci.3529-15.2016
|View full text |Cite|
|
Sign up to set email alerts
|

QuakingRegulatesNeurofascin 155Expression for Myelin and Axoglial Junction Maintenance

Abstract: RNA binding proteins required for the maintenance of myelin and axoglial junctions are unknown. Herein, we report that deletion of the Quaking (QKI) RNA binding proteins in oligodendrocytes (OLs) using Olig2-Cre results in mice displaying rapid tremors at postnatal day 10, followed by death at postnatal week 3. Extensive CNS hypomyelination was observed as a result of OL differentiation defects during development. The QKI proteins were also required for adult myelin maintenance, because their ablation using PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…Experimental protocols involving animal use were approved by the McGill University Animal Care Committee. QKI FL / FL ; Olig2 - Cre and QKI FL / FL ;- mice were generated as described 2 . Exon 2 of the qkI gene is flanked with loxP sites and the recombination with Cre results in a null.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocols involving animal use were approved by the McGill University Animal Care Committee. QKI FL / FL ; Olig2 - Cre and QKI FL / FL ;- mice were generated as described 2 . Exon 2 of the qkI gene is flanked with loxP sites and the recombination with Cre results in a null.…”
Section: Methodsmentioning
confidence: 99%
“…The deletion of the QKI isoforms in OLs using Olig2-Cre ( QKI FL / FL ; Olig2 - Cre ) leads to severe CNS hypomyelination with tremors by post-natal day 10 (P10) and death at the third post-natal week. Ablation of qkI in adult mice using PLP-CreERT results in hindlimb paralysis, thoracic kyphosis and immobility by the third to fourth week post-4-hydroxytamoxifen (OHT) administration 2 . This work defines the QKI isoforms as major regulators of OL differentiation and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…In the nervous system, Qki proteins are predominantly expressed in oligodendrocyte lineage cells (Hardy et al 1996;Hardy 1998) and are key regulators of oligodendrocyte differentiation and myelination. These effects are mediated by RNA-level regulation of cell cycle-and myelin-related genes (Larocque et al 2002(Larocque et al , 2005Wu et al 2002;Darbelli et al 2016). In addition, our immunohistochemical analysis in the present study and a previous report revealed unique cellular distributions of these proteins during brain development ( Fig.…”
mentioning
confidence: 99%
“…Nfasc155 is known to be present at axoglial junctions in the spinal cord. By crossing QkI FL/FL with PLP-CreERT and inducibly deleting the quaking gene in adult mice, the investigators found defects in axoglial junctions of the spinal cords and notable loss of Nfasc155 staining [17]. Therefore, these conditional mutant mice have been used to uncover a splicing change which results in a phenotypic defect.…”
Section: Quakingmentioning
confidence: 99%
“…Genetically modified animals are very informative in vivo models to answer these questions. Currently, there are viable homozygous knockout mouse models for all the STAR proteins except SF1 which can be exploited to study alternative splicing in an intact organism (the Sf1 null mouse is lethal) [11][12][13][14][15][16][17]. The brain has been shown to have the largest amount of alternative splicing in the body [18], perhaps because of its complex function.…”
Section: Introductionmentioning
confidence: 99%